Evolution of the event horizon of binary mergers in modified gravity - Rocha, J. V. (24th International Conference on General Relativity and Gravitation & 16th Edoardo Amaldi Conference on Gravitational Waves, 2025)
The collision of compact objects, such as black holes and neutron stars, is a spectacular cosmic event of great interest to gravitational wave astronomy. In recent years elementary ray-tracing techniques have been shown to capture the main characteristics of black hole mergers by considering the extreme mass ratio limit in an unorthodox way. In this regime, the evolution of the event horizon, when a large black hole merges with a small compact object, can be easily computed (semi-)analytically. In this talk, this approach will be exploited in the context of compact object mergers in modified gravities respecting the equivalence principle. Several examples will be discussed: the collision between two black holes in cubic gravity, the merger of two hairy black holes in Einstein-scalar-Gauss-Bonnet theory, and the fusion between a large black hole and a small traversable wormhole supported by a phantom scalar field. Differences with respect to black hole mergers in General Relativity will be highlighted.